(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Competency-based education (CBE) has emerged as a transformative approach in higher education, aiming to provide a more personalized and effective learning experience. This scientific article explores the concept of competency education in higher education institutions, discussing its principles, benefits, challenges, and the impact on student outcomes. By focusing on learners’ mastery of specific skills and knowledge rather than traditional time-based models, competency education seeks to prepare students for the dynamic demands of the 21st century workforce. The article also examines various implementation models, assessment strategies, and the role of technology in facilitating competency-based learning. Through a comprehensive review of the current literature, this article aims to contribute to the understanding and advancement of competency education within the higher education landscape. Competency education has emerged as a transformative approach in higher education institutions, reshaping traditional teaching and learning methods. This article explores the concept of competency education, its implications for higher education, and the potential benefits it offers in fostering a more personalized and student-centered learning environment. Through an examination of key principles, challenges, and successful implementations, this article aims to contribute to the ongoing discourse on innovative educational models that prepare students for the complexities of the 21st century workforce.